A review of allelopathy on microalgae. Issue 6 (28th January 2019) - Tan, Kaiting; Huang, Ziqi; Ji, Ruibo; Qiu, Yongting; Wang, Zhihong; Liu, Junxia
Abstract : Algal blooms have severe impacts on the utilization of water resources. The discovery of allelopathy provides a new dimension to solving this problem due to its high efficiency, safety and economy. Allelopathy can suppress the growth of microalgae by impairing the structure, photosynthesis and enzyme activity of algal cells. In the current work, we first demonstrate the allelopathy and allelochemicals derived from both plants and algae. We then expound the potential mechanisms of allelopathy on microalgae. Next, the potential application of allelochemicals in water environment is proposed. Finally, the key challenge and future perspective are presented.